Labor Markets, Inequality and Poverty in Georgia - Ruslan Yemtsov (Institute for the Study of Labor (IZA), 2001)
The labor market is the main channel through which economic growth affects poverty. This paper is the first empirical account of main channels through which the growth in transition period has affected labor market and living standards in Georgia. It is based on both the official aggregate statistics and data from a representative household survey fielded in 1996-1997. The paper finds that in Georgia the labor market has shown outstanding flexibility during a period of severe political and economic turmoil in 1992-1995. Despite the catastrophic fall in GDP employment contracted only marginally. This flexibility has been achieved mainly through the informalization of employment, and through the reallocation of labor towards small-scale agriculture. Informalization has dampened the impact of the crisis and served to protect the poor, stabilizing the poverty rate at the politically and socially acceptable level (around 15% of the population). However, the informalization limited the impact of market forces favoring human capital accumulation on the formation of earnings. Today, a large and growing fraction of the Georgian labor force relies on self-employment as the primary means to earn an income. For some, this is an avenue for earnings mobility and growth; for the majority, however, selfemployment remains constrained to low-productivity agricultural or trading activities, with little earnings stability and little potential for long term earnings growth. Prospects for the future hinge critically on the economy?s ability to generate new private formal employment, and to reallocate labor away from these low-productivity activities into higher value added sectors.
Keywords: I3; J4; 330; Employment; unemployment; informal sector; real wage; productivity; earnings; inequality; returns to education; poverty; gender gap; Übergangswirtschaft; Beschäftigungseffekt; Arbeitsmarktflexibilisierung; Informeller Sektor; Einkommensverteilung; Armut; Georgien